(untitled) (Journal of the College of Basic Education, 2023)
Due to the great scientific progress and the technology and informatics revolution in all areas of life and all specialties, and the entry of computers and the Internet in all aspects of life until it became part of the life of some individuals, and physical education in the developed world at the present time has achieved great progress in reaching sporting achievements as a result of the continuous effort made by Scientists interact with the sciences of physical education with the sciences of physics, physiology, anatomy, chemistry, psychology and others, in order to raise the level of achievement and its continuity. In addition to his mastery of joint teamwork, which consists of applying the developed plans, whether offensive or defensive, like any other team game that may exceed it in the large number of types used in one match due to the difficulty of the game and the large number of changes in it, and the player must highlight his playing skills as well About his proficiency in the directives and plans of his coach, so the importance of the research came in that the players implement t The instructions of their coaches during the match and during the rest periods between the halves after discovering the opponent’s plans and the mistakes of some of his players, in addition to the mistakes of some of the team’s players